Ethics, Educational Research and Training of Researchers: Between the Norm and the Project of Life - María Guadalupe Moreno Bayardo; Miguel Agustín Romero Morett (Universidad Autónoma de Madrid, 2016)
As far as the review of everyday practices, this article show how, far beyond the classic "ethic vices" acknowledged - such as plagiarism- the diverse performance of the researchers and tutors have behind them "lived ethic" from making the decision of becoming a tutor, to the different levels of commitment assumed with this task, or in the way of evaluating or devaluating the possibility of someone becoming a researcher. Thus, this article is woven within the conceptual and the existential leading to a natural ethical proposal delivered from the above exposed.